Implementation of Character Education For Increase Behavior in Grade IV Elementary School Students - Anugraini, Asri Putri; Avianty, Donna (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Moral degradation in the educational environment is the background of this study. One of the causes of moral degradation is education that prioritizes cognitive aspects rather than affective aspects. Character education is one of the efforts to improve student behavior. The application of character education has been optimally implemented at SD Negeri 3 Panggungrejo Kepanjen in the hope of improving student behavior. This study aims to determine how character education improves the behavior of grade IV students at SD Negeri 3 Panggungrejo Kepanjen. This study is a qualitative descriptive study. The subjects in this study were grade IV teachers and grade IV students at SD Negeri 3 Panggungrejo Kepanjen and the objects in this study were the application of character education in grade IV of SD Negeri 3 Panggungrejo Kepanjen and Student Behavior. Data collection was carried out through interviews, observations, and documentation. For this reason, the instruments created were in the form of interview guidelines for teachers and students, observation guidelines for teachers and students, and documentation analysis guidelines. Furthermore, the findings of the research data were analyzed through a series of qualitative analysis. The results of the study show that character education can help improve student behavior. Character education improves student behavior through habituation and role models carried out by teachers to students.